2018
DOI: 10.1111/jfpe.12815
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network for prediction of dielectric properties relevant to microwave processing of fruit juice

Abstract: Dielectric properties are fundamental parameters to determine the heating behavior of food products using microwaves. Determining and modeling these properties as a function of process conditions and product composition is required to be implemented in Multiphysics modeling, in which heat transfer and electromagnetic aspects are solved, allowing the characterizing and optimization of microwave processing. This work evaluates the dielectric properties of model fruit juice solutions at concentrations ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…According to other studies, sugar could not be detected in the chemical analysis of SCG as it is commonly extracted through the coffee brewing process. 24,25 However, the sugar content was found to be the most signicant component to model dielectric properties in products such as grapes or juices; 26,27 thus, the absence of it in SCG could diminish the dielectric constant values.…”
Section: Effect Of Moisture On Dielectric Constantmentioning
confidence: 99%
“…According to other studies, sugar could not be detected in the chemical analysis of SCG as it is commonly extracted through the coffee brewing process. 24,25 However, the sugar content was found to be the most signicant component to model dielectric properties in products such as grapes or juices; 26,27 thus, the absence of it in SCG could diminish the dielectric constant values.…”
Section: Effect Of Moisture On Dielectric Constantmentioning
confidence: 99%
“…For an appropriate and uniform pasteurization process, it is crucial selecting of frequency ranges. In previous studies, it was revealed that dielectric constants of liquid foods decreased as frequency and temperature increased (Nelson and Trabelsi, 2012;Siguemoto and Gut, 2016;Franco et al, 2017;Kubo et al, 2018;Gonzalez-Monroy et al, 2018;Sobreiro et al, 2018;Kumar and Shrivasta, 2019). The effects of applied frequency and temperature on loss factor values, may vary (Table 7).…”
Section: Liquid Foodsmentioning
confidence: 97%
“…Moreover, the sugar content of liquid foods is another important factor in dielectric properties. It was indicated that as Brix increases, although dielectric constant and penetration depth decrease, loss factor increases (Siguemoto and Gut, 2016;Franco et al, 2017;Kubo et al, 2018;Sobreiro et al, 2018;Kumar and Shrivasta, 2019).…”
Section: Liquid Foodsmentioning
confidence: 99%
“…Dans ce cas, la dégradation de l'énergie de l'onde électromagnétique en chaleur est due à la conductivité électrique des ions présents dans les matrices. A l'inverse, à la fréquence de 2450 MHz, les mécanismes lies à la rotation dipolaire des molécules sont majoritaires (Kubo et al, 2018a).…”
Section: Généralités Sur Les Mécanismesunclassified